1995
DOI: 10.1016/0896-6273(95)90243-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that pioneer olfactory axons regulate telencephalon cell cycle kinetics to induce the formation of the olfactory bulb

Abstract: Early olfactory axons follow a specific pathway to reach the developing telencephalon. We observed that a subpopulation of these axons, the pioneer olfactory axons, penetrate into the ventricular zone of a highly restricted region of the telencephalon at E13 and E14. At E15, this same telencephalic region evaginates to form the olfactory bulb. To investigate the possibility that the pioneer olfactory axons induce the olfactory bulb by influencing precursor cell populations, we compared cell cycle kinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
200
0
9

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(220 citation statements)
references
References 39 publications
11
200
0
9
Order By: Relevance
“…: the OE should dictate OB development from the first moment, as has been suggested by some authors. 26,27,39 However, none of these authors have proposed that a similar relationship might exist between the OB and the olfactory cortex, perhaps because of the well known studies regarding the triggering of neurogenesis in the cortex. 18,31,37 Shouldn't these studies be discussed in the context of the development of the olfactory system or when arguing in favor of a sequential series of events between the OE and OB?…”
Section: Mutual Influences Between Oe and Obmentioning
confidence: 99%
See 1 more Smart Citation
“…: the OE should dictate OB development from the first moment, as has been suggested by some authors. 26,27,39 However, none of these authors have proposed that a similar relationship might exist between the OB and the olfactory cortex, perhaps because of the well known studies regarding the triggering of neurogenesis in the cortex. 18,31,37 Shouldn't these studies be discussed in the context of the development of the olfactory system or when arguing in favor of a sequential series of events between the OE and OB?…”
Section: Mutual Influences Between Oe and Obmentioning
confidence: 99%
“…26 However, this relationship has not been so intensely studied in mammals, although it has been shown that the arrival of olfactory axons does appear to have a dramatic influence on cell kinetics and the rate of precursor differentiation in the OB-anlage. 27 It has been also suggested that inductive interactions from the frontonasal-mesenchyme are essential for the morphogenesis of both the OE and the OB. 5,28 However, such work has not been extended to the very early stages of the olfactory placode formation.…”
Section: Mutual Influences Between Oe and Obmentioning
confidence: 99%
“…Dans cette hypothèse, l'absence de développement des bulbes olfactifs serait secondaire à l'absence d'un contact stable entre les terminaisons des axones olfactifs et le cerveau, contact dont on sait depuis longtemps qu'il est nécessaire à la morphogenèse des bulbes olfactifs [19]. L'étude du profil d'expression précoce de l'anosmine-1 dans le système olfactif a révélé que durant la 6 e semaine du développement embryonnaire, la protéine est présente dans la matrice interstitielle des bulbes olfactifs présomptifs, au pôle rostral du télencéphale [12].…”
Section: La Pathogénie De L'anosmie Du Syndrome De Kallmann De Morsieunclassified
“…locale de la prolifération cellulaire [19] (Figure 4). Dès que l'orthologue de KAL1 aura été identifié chez la souris, l'inactivation du gène dans cette espèce devrait permettre d'étayer l'hypothèse unificatrice que nous proposons en montrant, chez les souris homozygotes mutantes, qu'il existe également un contact primaire des fibres olfactives avec le télencéphale, mais que l'étape initiale de la morphogenèse des bulbes olfactifs est défectueuse.…”
Section: La Pathogénie De L'anosmie Du Syndrome De Kallmann De Morsieunclassified
See 1 more Smart Citation